Application of Silica Nutrients Improves Plant Growth and Biomass Production of Paddy under Saline Conditions - Nasrudin Nasrudin; Arrin Rosmala; Rachmanto Bambang Wijoyo (Caraka Tani: Journal of Sustainable Agriculture, 2022)
Salinity makes disorder to plant physiological causes decreasing in biomass production. Applying silica nutrients is expected to increase paddy (Oryza sativa L.) tolerance to salinity. The study aims to examine the effects of the application of silica nutrients under saline conditions regarding plant growth analysis and its correlation to paddy biomass production. The research was arranged in a factorial completely randomized design with two factors. The first factor was NaCl concentrations consisting of four levels, including non-saline, 4 dS m-1, 8 dS m-1 and 12 dS m-1. The second factor was silica doses per kg soil with three levels including 300 mg, 450 mg and 600 mg. The treatments were repeated three times. The result showed that the NaCl concentration affected root shoot ratio at harvest. Silica dosage affected leaf area index 8 weeks after planting (WAP), root shoot ration at harvest and net assimilation rate. Interaction of NaCl concentration and silica dose affected root shoot ratio in 8 WAP and at harvest. Plant growth analysis illustrated on leaf area index, plant growth rate and root shoot ratio correlated positively with biomass production. However, the harvest index and net assimilation rate showed negative correlations to biomass production. The application of silica nutrients had the potential to improve paddy growth and yield under saline conditions.